Rhetorical Perspectives of Undergraduate Students’ Thesis Abstracts - Siyaswati Siyaswati; Dyah Rochmawati (IAIN Salatiga, 2017)
The present article aims at describing the students’ theses abstracts viewed from the rhetorical perspectives. It examines whether the abstracts provided in the university website include the essential rhetorical moves and whether the moves are presented in the sequence according to Hyland’s five-move classification (Introduction, Purpose, Method, Product, and Conclusion) of rhetorical moves. Eighty abstracts of the research articles written by the students were collected using purposive sampling. The frequency of occurrence of each move was statistically calculated and tallied. Two ESL (English as a second language) researchers validated the data classification. The findings revealed that 53.75% of the abstracts were found out to be written in accordance with the structure. Most abstracts give information on the purpose, methodology, and findings of the associated article. About half of the articles omit introduction of the topic and discussion of the findings. Moves “product” and “conclusion” were missing in a few abstracts. The students’ lengthy “introduction” move and over brief “product” move were found in most abstracts. Some rhetorical moves appeared to have higher incidence of occurrences than the others. The findings lend further insights into the needs of professional development among academics, particularly in academic research report writing. Keywords: rhetorical moves, student’s article abstracts INDONESIAN ABSTRACT Artikel ini bertujuan untuk mendeskripsikan abstrak skripsi mahasiswa dilihat dari sudut pandang retorik- meneliti apakah abstrak-abstrak tersebut memiliki ‘rhetorical moves’ yang esensial dan apakah ‘rhetorical moves’dipresentasikan dalam urutan sesuai dengan klasifikasi lima langkah Hyland (Pendahuluan, Tujuan, Metode, Produk, dan Kesimpulan) gerakan retoris. Delapan puluh abstrak artikel penelitian yang ditulis oleh siswa dikumpulkan dengan menggunakan purposive sampling. Frekuensi terjadinya setiap ‘move’ dihitung. Dua peneliti ESL (bahasa Inggris sebagai bahasa kedua) memvalidasi klasifikasi data. Temuan menunjukkan bahwa 53,75% abstrak ditemukan ditulis sesuai dengan strukturnya. Sebagian besar abstrak memberikan informasi tentang tujuan, metodologi, dan temuan dari artikel yang terkait. Sekitar setengah dari artikel menghilangkan pengenalan topik dan diskusi tentang temuan. Tidak terdapat Move